Pengaruh sumber pembiayaan desentralisasi fiskal terhadap Produk Domestik Regional Bruto dan tingkat kemiskinan (Studi di kabupaten-Kota di Provinsi Jambi) - Agung Ridwan; Syaparuddin Syaparuddin; Candra Mustika (Jurnal Paradigma Ekonomika, 2017)
This study aims to analyze: 1) sources of financing for fiscal decentralization, GRDP and poverty levels of regencies / cities in Jambi Province (2) the effect of sources of fiscal decentralization financing on gross domestic product in regencies and cities in Jambi Province (3) the effect of fiscal decentralization financing sources towards poverty levels in regencies and cities in Jambi Province. The analysis period is 2007 - 2013. To analyze the influence of the sources of fiscal decentralization funding on GRDP and poverty levels, using two panel data regression models. The results of the analysis found that: 1) During the 2007-2013 period, the sources of financing for fiscal decentralization consisting of Local Original Revenue, Balanced Funds and Other Other Income in regencies and cities in Jambi Province generally increased every year; 2) The GRDP regency-city growth in Jambi Province is fairly high with an average of 6.83%, higher than the national economic growth; 3) In general, the poverty rate of regencies/cities in Jambi Province has decreased significantly every year during the period 2007 – 2013. Original Regional Revenue and other legitimate income have a negative and significant effect while the balance fund does not have a significant effect on the poverty level of regencies/cities in Jambi Province.